Human CD8 T cells generated in vitro from hematopoietic stem cells are functionally mature - Zúñiga-Pflücker Juan; La Motte-Mohs Ross N; Herer Elaine; Awong Génève (BMC Immunology, 2011)
Abstract Background T cell development occurs within the highly specialized thymus. Cytotoxic CD8 T cells are critical in adaptive immunity by targeting virally infected or tumor cells. In this study, we addressed whether functional CD8 T cells can be generated fully in vitro using human umbilical cord blood (UCB) hematopoietic stem cells (HSCs) in coculture with OP9-DL1 cells. Results HSC/OP9-DL1 cocultures supported the differentiation of CD8 T cells, which were TCR/CD3hi CD27hi CD1aneg and thus phenotypically resembled mature functional CD8 single positive thymocytes. These in vitro-generated T cells also appeared to be conventional CD8 cells, as they expressed high levels of Eomes and low levels of Plzf, albeit not identical to ex vivo UCB CD8 T cells. Consistent with the phenotypic and molecular characterization, upon TCR-stimulation, in vitro-generated CD8 T cells proliferated, expressed activation markers (MHC-II, CD25, CD38), secreted IFN-γ and expressed Granzyme B, a cytotoxic T-cell effector molecule. Conclusion Taken together, the ability to direct human hematopoietic stem cell or T-progenitor cells towards a mature functional phenotype raises the possibility of establishing cell-based treatments for T-immunodeficiencies by rapidly restoring CD8 effector function, thereby mitigating the risks associated with opportunistic infections.